Micropropagation Of Meyer Lemon (Citrus X Meyeri) - Haradzi, Najwa Amalina (2019)
Citrus x meyeri or Meyer lemon is the hybrid of true lemon and sweet orange (Citrus limon x Citrus sinensis) and native to China. The ingestion of Meyer lemon fruits is not only for its sweet flavour, but also for its high amounts of vitamin C and bioactive compounds that serve as antioxidant and anti-inflammatory agents. Current conventional techniques such as grafting and cutting used to propagate Meyer lemon in Malaysia were found to be less efficient for the production of plant stocks for commercial purposes. This study was aimed to establish in vitro protocol to mass propagate Meyer lemon through multiple shoot induction and to evaluate somatic embryogenesis formation. Surface sterilization was conducted on shoot tip and seed explants with agitation in 70% (v/v) of ethanol and different concentrations of Clorox® solution. Axenic shoot tips were inoculated in ½ strength Murashige and Skoog (MS) media with different cytokinin (BAP, Kinetin, Zeatin and Thidiazuron) and combinations of BAP with auxin, NAA and IAA. Root induction was performed in ½ strength MS and WPM media with different auxin, IAA and IBA. The well rooted shoots were acclimatized in black garden, red burnt and biochar soil mixture (2:1:1). Polymorphism analysis was carried out between cultivated and different subcultures of shoots using ISSR and SCoT markers. Light illumination, supplementation of single 2,4-D and combinations 0.5 mg/L 2,4-D with cytokinin (BAP, Kinetin and TDZ) were assessed for embryogenic callus formation using epicotyl segments from in vitro germinated seedlings. Similarly, light illumination and different cytokinin (BAP, Kinetin and TDZ) supplementation were also investigated for somatic embryos induction.